The Order of Community Service as an Alternative Punishment in the Shariah Court of Malaysia: (Perintah Khidmat Masyarakat Sebagai Hukuman Alternatif di Mahkamah Syariah Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2014)
The punishment for the offence of shariah crime in Malaysia nowadays is still based on three years of imprisonment, penalty of RM5000 and six times of whipping. Those maximum punishments are always been questioned due to its ineffectiveness in giving positive impacts either to the offenders or society. In encountering such situation, the alternative punishments may be enforced by the shariah court so that the objective of the punishment could be achieved. Therefore, there is suggestion that want to materialize the punishment based on community service order, as one of the alternative punishment in the shariah court. In relation to that, this article aims to view the extent of the implementation of the community service order in the shariah law framework by looking at the current prospect in implementing the punishments. After reviewing the need of the punishment, the research discovers that the community service order has great prospect to be enforced at the shariah court, through the existing provisions. This research is important because it portrays that the community service order has a potential to be implemented as one kind of the best alternative punishment at the shariah court of Malaysia.Keywords: community service order, alternative sentence, provisions of the law, shariah court in Malaysia